(untitled) (The Nepalese Management Review, 2024)
This study examines the satisfaction level of Management students towards online classes during covid-19 pandemic in T.U. The effect of Covid-19 on educational institutions has interrupted the traditional method of teaching and learning which ultimately created the demand of online classes. This study aims to find out the perception and satisfaction of MBS Program students who have attended their classes through online mode during the Covid-19 pandemic. To achieve the research objective, the data were collected from the primary source mainly through structure questionnaire under convenience sampling basis from 384 respondents of MBS students of Kathmandu valley who has attended the online classes. Pearson correlation and multiple regression analysis has been used to determine the relationship and impact of the dimension of online classes and the satisfaction level of students. The study revealed that technology plays an important role for the effectiveness of online classes which supports for the enhancement of the satisfaction level of students towards online classes. The study showed that due to the frequently power cut off and unstable internet network problems faced by the students during their online classes. The internet facility available for teaching and learning activities is not so good so that the level of satisfaction of the students towards online classes is decreased. The study also revealed that the instructors and learners both should be updated with the latest and modern technology for the effectiveness of the online classes.